(untitled) (Książnica Śląska, 2025)
The article describes the latest graphic acquisition of the Silesian Library – “Teka wojenna (Portfolio of the War) 1914–1915” made by students of the 1st c. k. Realschulle in Lviv under the supervision of Prof. Chrząstowski. The article discusses the lithographs of students and presents the figure of the professor of drawings Franciszek Chrząstowski, the initiator of the creation of the portfolio and the artist-pedagogue responsible for the process of its creation. The ownership mark (ex-libris by Zbigniew Jozwik) placed in the album and made for the Warsaw bibliophile, collector and numismatic of Lech Kokocinski was also described. The author of the paper tried to decipher the manuscript entry on the title card of the portfolio. This interesting publication is a valuable addition to the bibliophile collection of Roman Chrząstowski (son of Franciszek), which is in the collection of the Silesian Library.